Trotz allem ... die deutschsprachigen Juden in Argentinien - Schwarcz, Alfredo José (Böhlau, 1995)
"Valuable contribution to immigration history examines background, economic integration, degree of adaptation and/or assimilation, interaction with older Jewish groups, retention of culture and language, and social and cultural institutions of German-speaking Jews in Argentina. Covers three groups of refugees who entered Argentina between 1933-45: immigrants over 18, under 18, and immigrants' children born in Argentina or neighboring countries. The author, a psychologist specializing in gerontology, was assisted by social scientists and supported by Jewish organizations"--Handbook of Latin American Studies, v. 58